A política de coesão territorial da União Europeia: tendências recentes em cenário de crise e desemprego - Aldomar A. Rückert; Adriana Pilar F. Albanus (Confins)
The article presents preliminary research results about the territorial cohesion policy of the European Union associated to recent territorial repercussions examining the financial crisis and unemployment. It analyzes the Policy and expenditure of the Structural and Cohesion Funds between 2001 and 2013 with particular emphasis to the problem of unemployment, especially in PIIGS countries - Portugal, Italy, Ireland, Greece and Spain - and in some of its regions with socioeconomic and sociocultural weaknesses. Thematic maps represent variables as the behavior of GDP per head, the public debt of Member States and taxes of unemployment in regional and national scales in the territory of the European Union.